2018
DOI: 10.1017/s1049023x18000043
|View full text |Cite
|
Sign up to set email alerts
|

Existing Approaches to Chemical, Biological, Radiological, and Nuclear (CBRN) Education and Training for Health Professionals: Findings from an Integrative Literature Review

Abstract: While the CBRN training course requires the participants to gain specific skills and knowledge, proposed training courses should be effectively constructed to include approaches such as scenario-based simulations, depending on the participants' needs. Kako M , Hammad K , Mitani S , Arbon P . Existing approaches to chemical, biological, radiological, and nuclear (CBRN) education and training for health professionals: findings from an integrative literature review. Prehosp Disaster Med. 2018;33(2):182-190.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 26 publications
0
34
0
1
Order By: Relevance
“…Complicating a straightforward emergency response is the addition of CBRN factors that add an extra layer of complexity to the emergency response. 21 CBRN emergencies cause trauma on a large scale and demand complex responses including triage, monitoring, diagnosis, decontamination, and self-protection for public health workers. 11,22 CBRN mass casualty situations are normally chaotic.…”
Section: Introductionmentioning
confidence: 99%
“…Complicating a straightforward emergency response is the addition of CBRN factors that add an extra layer of complexity to the emergency response. 21 CBRN emergencies cause trauma on a large scale and demand complex responses including triage, monitoring, diagnosis, decontamination, and self-protection for public health workers. 11,22 CBRN mass casualty situations are normally chaotic.…”
Section: Introductionmentioning
confidence: 99%
“…Literature reviews have shown that specific training to respond to future crises involving CBRN substances is only offered in a few healthcare programmes, mostly in the United States (US) [17]. There is also very little peer-reviewed literature or guidelines that provide an outline of specific learning objectives and activities to implement and deliver this training to face future crises; particularly amongst clinicians and other health professionals that would be part of an initial response [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is imperative that health professionals that will be the first-response workforce, i.e. nurses, doctors, paramedics, biomedical scientists, physician associates, and public health officers, have the necessary skills to effectively respond to HazMat/CBRN threats [17].…”
Section: Introductionmentioning
confidence: 99%
“…A critical step in the aftermath of a biological incident or accident (accidental or deliberate release of a biological hazard) is to decontaminate and recover the affected environment [2,3]. Biological incidents can affect different areas and environments, requiring cross-government efforts and special tools and agents to decontaminate [4], in conjunction with personnel appropriately trained and skilled to respond to the incident [5]. Despite medical doctors and related health care professionals and public health officers providing the first-response to incidents involving biological threats, recent studies have reported insufficient knowledge or skills to respond to these events by many such personnel [5].…”
Section: Introductionmentioning
confidence: 99%